Establishing grading indices of available soil potassium on paddy soils in Hubei province, China. Issue 1 (December 2018) - Li, Xiaokun; Zhang, Yangyang; Wang, Weini; Khan, Muhammad; Cong, Rihuan; Lu, Jianwei
Abstract Soil testing is an important diagnostic tool for assessing crop-available soil potassium (K) and hence making appropriate fertilizer recommendation. This study was aimed at correlating grain yield response data to soil-test K extracted with ammonium acetate (NH4 OAc), cold nitric acid (HNO3 ), sodium tetraphenylboron (NaTPB) and boiling HNO3 solution, based on 54 field trials conducted during 2011 to 2015 across 15 counties in Hubei province, China. The specific objectives were to establish abundance and deficiency indices of available soil-K (ASK) for rice (Oryza sativa L.) and make accurate K fertilizer recommendations. Potassium extracted with NaTPB and boiling HNO3 was 1.47 times and 3.61 times higher respectively than that extracted with cold HNO3, while K extracted with cold HNO3 was 1.32 times higher than that extracted with NH4 OAc. There were significant logarithmic relationships between crop response and soil-test K. The R2 values for cold HNO3 -K and NaTPB-K methods were much higher than for NH4 OAc-K method. In order to calibrate the application, the abundance and deficiency indices of ASK categorized by cold HNO3 -K in low, medium, high and very high ranges were <50 mg kg−1, 50 to 100 mg kg−1, 100 to 200 mg kg−1 and >200 mg kg−1 respectively, and that defined by NaTPB-K were <60 mg kg−1, 60 to 150 mg kg−1, 150 to 330 mg kg−1 and >330 mg kg−1, respectively. These values could be used to evaluate soil K supplying capacity and make appropriate K fertilizer recommendations for rice.